GENERASI MUDA SADAR BISING (GEMA DARING) PADA PELAJAR SMA - SMK DI KOTA DENPASAR - K.A.D. Saputra; I.P.S. Dewantara; W. Suardana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Objective: To increase knowledge and awareness about the risk of noise-induced hearing loss as a promotive effort in preventing noise-induced hearing loss among high school and vocational high school students in Denpasar City. Methods: Implementation of webinars and online workshops on the introduction and treatment of noise-induced hearing loss in high school and vocational high school students in Denpasar City. The increase in knowledge in this activity is assessed by the results of the pre-test and post-test. Results: A webinar and workshop